Estudio de la demanda de automóviles y su relación con el ingreso familiar de los habitantes de la provincia de Chimborazo durante el período 2012-2013. - Erazo Arce, Víctor Silverio (2016)
The supply and demand for a good is important in the economic market analysis, and present research income level of families in the province of Chimborazo was studied, and how are you can buy a new car, from a situational analysis to measure the contribution and compliance activities, qualitatively, quantitatively the results obtained from field observation and implementation of household surveys in the province of Chimborazo. This research entitled "Study of the demand for automobiles and their relationship to the family income of the inhabitants of the province of Chimborazo during the period 2012 - 2013" is divided into five chapters are structured as follows: The first chapter corresponds to the benchmark, where is the formulation and approach to the problem, objectives, both general and specific, in addition to the justification of the research developed, taking into account the realities of the place in which it developed the research. In the second chapter, the theoretical framework discussed in the literature of several books, journals, reports and newsletters delivered by the National Institute of Statistics and Censuses of Ecuador, as well as consultation of web pages was considered. This chapter covers different units that helped in the development of this research, and analyzes as units supply and demand, income level, the automotive market in Ecuador and Chimborazo Province, and the characteristics of the study site. The third chapter is the methodological framework in which methods, techniques are covered to follow for the proper handling of information obtained, and for determining the sample while checking hypothesis. In the fourth chapter the results of the research are exposed, making a comparative analysis of recent years, and studying the income of families in the province of Chimborazo, plus a projection which will be held demand for vehicles coming years in the province. In the fifth chapter the conclusions and recommendations arises in this chapter the conclusions and recommendations that it came to this research are reflected.